South Africa’s High-stress Security Environment: Keys to Coping (Gerhard Schoeman) - Bester, Piet (Scientia Militaria - South African Journal of Military Studies, 2025)
South Africa’s High-stress Security Environment: Keys to Coping by Gerhard Schoeman, Pretoria: UNISA Press, 2023, 106 pages, ISBN 978-1-7761-5183-7.